2020
DOI: 10.1126/sciadv.abc6601
|View full text |Cite
|
Sign up to set email alerts
|

Layer-engineered large-area exfoliation of graphene

Abstract: The competition between quality and productivity has been a major issue for large-scale applications of two-dimensional materials (2DMs). Until now, the top-down mechanical cleavage method has guaranteed pure perfect 2DMs, but it has been considered a poor option in terms of manufacturing. Here, we present a layer-engineered exfoliation technique for graphene that not only allows us to obtain large-size graphene, up to a millimeter size, but also allows selective thickness control. A thin metal film evaporated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
58
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(60 citation statements)
references
References 43 publications
1
58
1
Order By: Relevance
“…The photos of the stages and the results of the lithography on few-layer graphene samples are shown in Figure 3 a–e. We used natural graphite and LLE method of mechanical exfoliation [ 31 ] to insulate mono- and few layers of graphene on oxidized Si (285 nm thermally grown wafer from Graphene Supermarket [ 32 ]). The Si wafer was heavily doped with boron to provide back-gating at the low temperatures.…”
Section: Materials and Methodsmentioning
confidence: 99%
“…The photos of the stages and the results of the lithography on few-layer graphene samples are shown in Figure 3 a–e. We used natural graphite and LLE method of mechanical exfoliation [ 31 ] to insulate mono- and few layers of graphene on oxidized Si (285 nm thermally grown wafer from Graphene Supermarket [ 32 ]). The Si wafer was heavily doped with boron to provide back-gating at the low temperatures.…”
Section: Materials and Methodsmentioning
confidence: 99%
“…In this method, a selective metal film was directly evaporated on bulk graphite precleaved on blue tape and then large-area graphene with a selected number of layers can be exfoliated easily. This LEE approach paves the way for the development of a manufacturing-scale process for future applications based on a 2D heterostructure (Figure 8c) [180].…”
Section: Mnbi 2n Te 3n+1mentioning
confidence: 98%
“…(c) Schematic illustration of the LEE large-area graphene exfoliation technique. Reused with permission from[180]. (d) Photographs of the dispersions of MoS2 (in N-methyl-pyrrolidone (NMP)), WS2 (in N-methyl-pyrrolidone (NMP)), and BN (in isopropanol (IPA)).…”
mentioning
confidence: 99%
“…Fortunately, it is shown that large-area mechanical exfoliation of graphene with controlled thickness can be achieved, as demonstrated recently in ref. 148 , showing high potential for the device development in the future. In order to develop high-performance Si/2DM PDs, more efforts at the material level are desired for the interface engineering, including contact engineering 149 , doping engineering, and strain engineering 12 , as shown in Fig.…”
Section: Perspective and Outlookmentioning
confidence: 99%